The Evaluation of serum Nestin and HOTAIR rs12826786 C>T polymorphism as screening tools for Breast cancer in Egyptian women: Serum Nestin and Breast Cancer - Elsammak, Mohamed; Awad, Ahmed; Aglan, Sarah; Elsammak, Omar; Gaber, Heba; Elbakoury, Eman; Sultan, Mohamed Hussein; Hamed, Yasser Sayed Ahmed (Journal of Medical Biochemistry, 2020)
Nestin; a neural stem cell protein that plays an important role in Cancer stem cells (CSC) development and proliferation. It has been identified as a marker for newly formed endothelial cells and was shown to be preferentially expressed in basal and myoepithelial cells of the mammary gland. HOTAIR is long intergenic non-coding (linRNA) associated with tumorigenesis through promotion of epithelial – mesenchymal transition (EMT) and stemness as well. HOTAIR gene contains a functioning single nucleotide polymorphic site rs12826786 C>T that has been associated with several cancer types.We evaluated serum Nestin and the HOTAIR rs12826786 C>T polymorphism, in healthy and breast cancer Egyptian women, for using as a possible screening tool to identify patients with breast cancer. Also, we tested the possible association of the two markers with each other and aggressiveness of the disease.Results: Patients with breast cancer had a median (Min-Max) of serum Nestin 31.3 (6.7 - 167.3 pg/ml) while control subjects had a median (Min-Max) of serum Nestin 42.3 ( 25.7-315.95) pg/mlThe best cut-off value for serum Nestin to differentiate normal subjects and patients with breast cancer was 39.9 pg/ml. This cut-off value had a diagnostic sensitivity of 84.8% and specificity of 65.1%.There was a significant difference in the distribution of different alleles in patients with breast cancer than normal subjects (P= 0.039 Exact Fisher test)The breast cancer patients group had 23% CC, 52.1%CT and 23.9% TT genotypes respectively while the control group had 46.9% CC, 42.8%CT and 10.2% TT respectively.Conclusion: A significantly low serum Nestin below 39.9 pg/ml and higher percentage of the T/T homozygous mutant allele of HOTAIR rs12826786 C>T were found in Egyptian patients with breast cancer. We suggest that the reported cutoff value of serum Nestin and the presence of C/T polymorphism can be used to assess the risk of females for developing breast cancer and might be of potential benefit in screening the disease. Larger studies in different ethnic groups are needed to confirm our findings.
Keywords: Nestin; HOTAIR